Budget politics in Indonesia: Processes, challenges, and economic implications - Hafel, Muhlis; Ibrahim, Abdul Halil Hi (International research journal of management, IT and social sciences, 2024)
Budget politics in Indonesia is a very complex process, ranging from central to local government. The budget planning process involves planning, approving, executing, and evaluating, all of which require close coordination and cooperation between institutions. The main challenges in Indonesia’s budget politics are the misallocation of funds, inequality between regions, growing debt, inflation, and unstable prices. The economic implications of inefficient budget politics are far-reaching. Imbalances between revenues and expenditures can increase the debt burden and interest costs, reducing the space for productive public spending. Inequalities in budget allocations can slow economic growth and increase social inequality. In addition, uneven financial decentralization exacerbates inequality between regions. Inflation rates fuelled by increased public spending without an increase in goods and services can reduce people’s purchasing power. Budget policy uncertainty also brings uncertainty for investors, which can reduce private investment and hamper economic growth. Overall, reforms in the budget distribution process, improved financial management capacity, and a commitment to inclusive and data-driven policies are urgently needed. These measures are essential to meet the challenges and ensure sustainable and equitable development for all Indonesians.